Pediatric scorpionism in southwest Turkey: the experience of a training and research hospital - Ayça Esra Akkaya Kuybulu; Duygu Çalışkan (Acta Medica Alanya)
Aim: The aim of this study was to evaluate the clinical and laboratory features and prognosis of scorpion stings in children.Methods: This was a retrospective study of children with scorpion stings, who were admitted to the pediatric emergency department in Alanya Alaaddin Keykubat University (ALKU) Training and Research Hospital between the 1st of January 2019 and the 31st of December 2020. Demographic data, admission date, time periods from sting to admission to hospital and geographical location in which the sting occurred were recorded. Recordings were also made of the affected body sites, local and systemic signs and symptoms of envenomation, results of hematological and biochemical laboratory tests, management, length of hospital stay and outcome.Results: In total, medical records of 111 children were reviewed. Patients were separated according to the clinical findings into three groups, seventy patients (63.1%) with mild symptoms and thirty-four patients (30.6%) with moderate symptoms, seven patients (6.3%) with severe symptoms. There was one exitus due to scorpion stings in the study period. Forty-one (37%) patients were hospitalised, and seven patients (6.3%) were hospitalised in the pediatric intensive care unit. Five patients (4%) received doxazosin and nineteen (17%) patients had antivenom therapy. Hospitalization in the intensive care unit was necessary for seven cases. No patient exhibited sequelae at the hospital discharge.Conclusions: Scorpion stings in our region mostly result in mild envenomation. Doxazosin, an analog of prazosin more readily available in our country, can be considered as a treatment option in serious scorpion envenomations with significant sympathetic symptoms.